Unravelling the last milliseconds of an individual graphene nanoplatelet before impact with a Pt surface by bipolar electrochemistry. Issue 37 (25th August 2021) - Deng, Zejun; Renault, Christophe
Abstract : The velocity of single GNP is monitored by contactless bipolar electrochemical feedback over the last hundreds of nm before collision on an electrode, and the variations shed light on the balance of forces acting on these objects near an interface. Abstract : Contactless interactions of micro/nano-particles near electrochemically or chemically active interfaces are ubiquitous in chemistry and biochemistry. Forces arising from a convective field, an electric field or chemical gradients act on different scales ranging from few microns down to few nanometers making their study difficult. Here, we correlated optical microscopy and electrochemical measurements to track at the millisecond timescale the dynamics of individual two-dimensional particles, graphene nanoplatelets (GNPs), when approaching an electrified Pt micro-interface. Our original approach takes advantage of the bipolar feedback current recorded when a conducting particle approaches an electrified surface without electrical contact and numerical simulations to access the velocity of individual GNPs. We evidenced a strong deceleration of GNPs from few tens of μm s −1 down to few μm s −1 within the last μm above the surface. This observation reveals the existence of strongly non-uniform forces between tens of and a thousand nanometers from the surface.